If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(230 + -0.5y) = 0 (230 * 2 + -0.5y * 2) = 0 (460 + -1y) = 0 Solving 460 + -1y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-460' to each side of the equation. 460 + -460 + -1y = 0 + -460 Combine like terms: 460 + -460 = 0 0 + -1y = 0 + -460 -1y = 0 + -460 Combine like terms: 0 + -460 = -460 -1y = -460 Divide each side by '-1'. y = 460 Simplifying y = 460
| 3x+10=-5x-19 | | 0.03-0.1y=0.05 | | 6x-18=x+12 | | 2e^6t=4e^5t | | (y+110)+30=180 | | -8(6x-1)+7(7x-3)-9=7-4 | | 2b-68+2b=180 | | 3y-1+y+37=6y+40-4y | | 2y+3x+3=0 | | (y+30)+110=180 | | (1+m)x^2-3mx+(1-m)=0 | | 3y-1+y+37y=6y+40-4y | | 6(4x+9)-23(x+5)=x-63 | | 2x+1=x+63 | | 3x+10=3x-19 | | 5x+4=-8+3x+2x | | 3y-1+y+3y=6y+40-4y | | y=7x+8kx | | 18x+15=4x+29 | | 10-k=12-1 | | 4p=p+14 | | 8-3h=5h+2 | | 17x^2-16x-12=0 | | -2r-6=12-4r | | -4x-12x=80 | | -6+19x=19x-6 | | 24h-6g= | | x+(x-35)=83 | | 9(x+2)=9(x+14) | | 6x^2+22x-5=0 | | 2x-(-10)=-5 | | 50x=6x-40 |